A short history of South Africa - Nattrass, Gail (2017)
A brief, general account of the history of South Africa that uncovers the first evidence of hominid existence to the wars of the eighteenth and nineteenth centuries that led to the establishment of modern South Africa, the horrors of Apartheid, and the optimism following its collapse, as well as the prospects and challenges for the future.
Includes bibliographical references and index.
Keywords: Apartheid -- South Africa; South Africa -- History